Oblicz wartość liczbową wyrażenia :

a) 4x - (x+6) + 4 dla x= 1/3 (jedna trzecia)
b)(x² + 1) - (x² - 2) + 10 dla x = 2,2
c) (a + 4b) - (5 + 2a) - (3b - 5) dla a= -0,1 i b= 0,2
d) (-a² + 2ab - 1) + ( a² - 4ab +5) dla a= 1/4 (jedna czwarta) i b=2.

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-28T16:26:42+01:00
4x - ( x + 6 ) + 4 = 4 * 1/3 - 1/3 - 6 + 4 = 4/3 - 1/3 - 2 = 1 - 2 = -1
( x2 + 1 ) - ( x2 - 2 ) + 10 = ( 4,84 +1 )- ( 4,84 - 2 ) + 10 = 5,84 - 2,84 + 10 = 13
(a + 4b) - (5 + 2a) - (3b - 5) = -0,1 + 0,8 - 5 + 0,2 - 0,6 + 5 = 0,3
( -a2 + 2ab - 1 ) + ( a2 - 4ab + 5 ) = 1 - 1 - 2 + 5 = 3